Introduction: the (im)material spectrum of manuscript and print interaction☆ - Norja, Sara; Varila, Mari-Liisa (Wiley, 2025)
This introductory essay to the special issue on Early Modern English Textual Cultures Between Manuscript and Print first outlines previous research into different kinds of interaction between manuscript and print. Examples of this interplay include, for instance, the transmission of text and images from one medium into another, the use of manuscript and print sources in the creation of new texts, works and codices, and readers annotating and copying printed sources by hand. We suggest that it is fruitful to consider both material and immaterial aspects of book production when investigating manuscript-print interactions. For instance, scribes copying printed sources may have prioritized the immaterial work being copied or imitated the material features of their exemplar. In our view, the material and the immaterial are intertwined throughout the process of book production. We conclude the introduction by briefly outlining the seven essays in the collection, which address various types of interaction between manuscript and print.